Effect of Immunoactive Drugs on Postresuscitation Processes in the Brain and Steroid Hormones - Yu. V. Zarzhetsky; V. V. Moroz; A. V. Volkov (Общая реаниматология, 2014)
Objective: to evaluate the effects of the immunostimulants panavir and derinate on a postresuscitation process in animals of different sexes.Material and methods. The investigation was made on 200—250-g albino rats of both sexes in winter. Circulation  was  stopped  by  intrathoracic  ligation  of  the  cardiac  vascular  bundle  in  ether<anesthetized  rats  for  10  min. Functional recovery of the central nervous system and changes in sex steroid hormones were assessed in the postresuscitation period. The investigation used two immunoactive drugs: panavir 0.02 mg/kg and derinate 150 μg/kg. Either agent was intramuscularly injected twice: at 3 0 minutes after resuscitation and on the following day.Results. The injected drugs were ascertained to have a positive effect on functional recovery of the brain. Their use was shown to modify the sex steroid hormone  profiles  in  both  males  and  females  in  the  early postresuscitation period.Conclusion. The findings suggest that the immunoactive agents are able to affect the nervous and  endocrine  systems  in  critical  conditions.